2009
DOI: 10.1007/s12105-009-0118-1
|View full text |Cite
|
Sign up to set email alerts
|

Primary Extracranial Meningiomas: An Analysis of 146 Cases

Abstract: Primary extracranial meningiomas are rare neoplasms, frequently misdiagnosed, resulting in inappropriate clinical management. To date, a large clinicopathologic study has not been reported. One hundred and forty-six cases diagnosed between 1970 and 1999 were retrieved from the files of the Armed Forces Institute of Pathology. Histologic features were reviewed, immunohistochemistry analysis was performed (n = 85), and patient follow-up was obtained (n = 110). The patients included 74 (50.7%) females and 72 (49.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
212
1
5

Year Published

2011
2011
2020
2020

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 148 publications
(218 citation statements)
references
References 52 publications
0
212
1
5
Order By: Relevance
“…A meningothelial pattern is not seen in ESSPA, but the presence of intranuclear cytoplasmic inclusions, a sheetlike to packeted growth, and isolated psammoma calcifications can raise the differential diagnosis of meningioma. However, meningioma is usually positive with EMA and CK7 (in a pre-psammoma body like pattern), while negative with neuroendocrine and pituitary hormone markers [68,69].…”
Section: Differential Diagnosismentioning
confidence: 99%
“…A meningothelial pattern is not seen in ESSPA, but the presence of intranuclear cytoplasmic inclusions, a sheetlike to packeted growth, and isolated psammoma calcifications can raise the differential diagnosis of meningioma. However, meningioma is usually positive with EMA and CK7 (in a pre-psammoma body like pattern), while negative with neuroendocrine and pituitary hormone markers [68,69].…”
Section: Differential Diagnosismentioning
confidence: 99%
“…An analysis of 146 cases of primary extracranial meningiomas showed that majority originated from the skin and scalp (n = 59) followed by middle ear (n = 26) and sinonasal tract (n = 25). Other rare locations in the head and neck included the temporal bone, mandible, nasopharynx, parotid gland, orbit and neck [5]. Different mechanisms have been proposed to explain the etiopathogenesis of these lesions.…”
Section: Discussionmentioning
confidence: 99%
“…Arachnoid islets displaced by trauma or cerebral hypertension 4. Undifferentiated mesenchymal cells [5].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations